Latex battery - Lau, Chiau Wee.
Basically, the latex battery is a new kind of battery, which works by the oxidation and reduction processes inside the battery with the latex as an electrolyte. This is a new way producing electricity by latex with two electrodes. The voltage and current are main parameter in this project. In this project, copper and zinc are selected as the electrodes. The optimum distance between the electrodes is 2.0 cm. The electrode area is at 4.9 x 5.6 cm2 fixed. All these physical settings are used with four latex samples: Field latex, Blended latex, fresh latex and High Ammonia latex. The battery arrangement plays an important role to provide the voltage required in order to operate a digital clock. The series arrangement was chosen to produce 1.5 volts which is enough to operate digital clock. The discharging process of latex battery is done by monitoring the voltage measure and this is through the computer interfacing system. This latex battery is being able to supply the power up to 7 - 8 days. The time showed on the LCD screen of the digital clock still clear after 8 days. It hoped that the research in this battery will be further developed and it can be used for various applications.